Efficacy of vitamin D in children with pneumonia: a randomized control trial study - Dhungel, A; Alam, MS (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: Pneumonia is the inflammation of parenchyma of lungs. It strictly represents any inflammatory condition that involves the lungs along with the visceral pleura, airways, alveoli, connective tissues and vascular structures. The objective of the study was to see the efficacy of vitamin D in children with pneumonia.Material and Methods: A randomized control study was conducted in Department of Pediatric Medicine, Mayo Hospital, Lahore, Pakistan. One hundred patients with pneumonia received vitamin D along with appropriate antibiotics and one hundred were treated with antibiotics but without vitamin D. The patients were discharged after the fast breathing and chest in drawing settled. The duration of hospital stay was noted. They were followed up for next 90 days after discharge from hospital and any new episode of pneumonia was noted and recorded.Results: The mean number of days to recovery were similar between the group receiving vitamin D (5.7 ± 2.7 days) and the group not receiving vitamin D (6.1 ± 2.8days), (p=0.28). While comparing repeat episode of pneumonia within next three months, the repeat episode of pneumonia was significantly lower in the intervention group (2%) than the group without supplementation (9%; p = 0.002) within 30 days of supplementation of vitamin D.Conclusion: Vitamin D supplementation in a single dose to the children diagnosed as pneumonia significantly reduces the occurrence of new episodes of pneumonia within one month of discharge.Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (1):5-13